(untitled) (Contextos: Estudios de Humanidades y Ciencias Sociales, 2019)
The aim of this study focuses not only on the inherent bilingualism of deaf children from the linguistic perspective but also the right of being educated in their mother tongue, especially understanding the role that language plays in both, the configuration and the settlement of Deaf culture in terms of deaf children’s educational experience. The purpose of this investigation is enhance educational approaches by means of a critical literature revision in order to broaden the discussion among researchers within the field of linguistics and education. By doing so, we try to broaden the scientific dissemination towards sign language in Chile and its role inside the classroom.